2021
DOI: 10.3390/molecules26020511
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Deiminase Induces Immunogenic Cell Death and Is Enhanced by N-acetylcysteine in Murine MC38 Colorectal Cancer Cells and MDA-MB-231 Human Breast Cancer Cells In Vitro

Abstract: The use of arginine deiminase (ADI) for arginine depletion therapy is an attractive anticancer approach. Combination strategies are needed to overcome the resistance of severe types of cancer cells to this monotherapy. In the current study, we report, for the first time, that the antioxidant N-acetylcysteine (NAC), which has been used in therapeutic practices for several decades, is a potent enhancer for targeted therapy that utilizes arginine deiminase. We demonstrated that pegylated arginine deiminase (ADI-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These elF2α kinase activators have been studied in cancer therapy. For example, Halofuginone and arginine deiminase were found to inhibit tumor growth, development and metastasis either as single agents or in combination with 5-FU or radiation (Abramovitch et al, 2004;Kim et al, 2009;Cook et al, 2010;Spector et al, 2010;Lamora et al, 2015;Brin et al, 2018;Singh et al, 2019;Wang et al, 2020;Huang and Hu, 2021). Our laboratory has identified two small molecules PG3-Oc (Tian et al, 2021) and ONC201 (Kline et al, 2016;Ishizawa et al, 2016) that suppress tumor growth through increased ISR signaling.…”
Section: Enhanced Integrated Stress Response Signaling Viamentioning
confidence: 98%
“…These elF2α kinase activators have been studied in cancer therapy. For example, Halofuginone and arginine deiminase were found to inhibit tumor growth, development and metastasis either as single agents or in combination with 5-FU or radiation (Abramovitch et al, 2004;Kim et al, 2009;Cook et al, 2010;Spector et al, 2010;Lamora et al, 2015;Brin et al, 2018;Singh et al, 2019;Wang et al, 2020;Huang and Hu, 2021). Our laboratory has identified two small molecules PG3-Oc (Tian et al, 2021) and ONC201 (Kline et al, 2016;Ishizawa et al, 2016) that suppress tumor growth through increased ISR signaling.…”
Section: Enhanced Integrated Stress Response Signaling Viamentioning
confidence: 98%
“…Furthermore, using murine MC38 colon cell model, it was shown that ADI-PEG20 is able to induce apoptotic and immunogenic cell death with the phenotypes of cell exposure of calreticulin, the release of HMGA1 and ATP, which is enhanced by N-acetylcystein [ 106 ]. These “eat me” signals resulted in increased phagocytosis by bone marrow-derived dendritic cells.…”
Section: Arginine and Immunomodulationmentioning
confidence: 99%
“…In addition, Somma et al found that G-quadruplex binders induced ICD in MDA-MB-231 breast cancer cells, accompanied by T-cell activation 140 . Furthermore, Huang et al indicated that the antioxidant N-acetylcysteine (NAC) enhanced not only the antitumor activity of polyglycolylated arginine deiminase (ADI-PEG20), but also the features of ICD, including HMGB1 and ATP secretion 19 . Nevertheless, the ICD inducers in clinical trials for breast cancer are limited so far.…”
Section: Hmgb1 Serves a Potential Target Breast Cancer Therapymentioning
confidence: 99%